2003
DOI: 10.1186/cc2365
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Correspondence: Dilek Memis ², dilmemis@mynet.com R123 APACHE = Acute Physiology and Chronic Health Evaluation; BIS = bispectral index; ICU = intensive care unit. AbstractIntroduction In intensive care unit patients we assessed, using bispectral index (BIS) monitoring, whether the addition of magnesium sulphate infusion could decrease the sufentanil infusion required to maintain sedation. Patients and methods A total of 30 adult patients who were expected to require machanical ventilation for 6 hours in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Memis D et al showed that magnesium sulphate had a sedative effect [26]. In the present study we found that patients who received magnesium sulphate were more sedated than the control group.…”
Section: Discussionsupporting
confidence: 58%
“…Memis D et al showed that magnesium sulphate had a sedative effect [26]. In the present study we found that patients who received magnesium sulphate were more sedated than the control group.…”
Section: Discussionsupporting
confidence: 58%
“…According to the Memiş et all. [24] while magnesium (2 g/h infusion) infusion was reducing sufentanil consumption, BIS values did not significantly change. Average BIS values were kept in the range of 61-88 in this study by titrating the dose of sufentanil infusion in groups.…”
Section: Discussionmentioning
confidence: 78%
“…[ 13 ] Marked antiadrenergic and antinociceptive effects are also attributed to magnesium due to antagonism of NMDA and calcium channels in various studies. [ 14 15 ] In the present study, under the highlights of magnesium effects, we aimed to find out a better sedative among propofol, midazolam, and dexmedetomidine in eclamptic patients admitted to ICU for postoperative ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…in his study on thirty adult patients demonstrated that magnesium sulfate infusion decreases sufentanil infusion requirements in mechanically ventilated patients without causing a significant difference in bispectral index values between the groups. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%